Предмет: Алгебра, автор: СтасЕфремов

Решите кто сможет...................................

Приложения:

Ответы

Автор ответа: NaZaRiO24
0
......................
Приложения:
Автор ответа: CVita
0
 sqrt[3]{x+3}- sqrt[3]{x-1}=1 \ - sqrt[3]{x-1}=1- sqrt[3]{x+3} \ 1-x=(1- sqrt[3]{x+3})^3 \ 1-x-(1- sqrt[3]{x+3})^3=0 \ 3+3 sqrt[3]{x+3}-3(x+3)^ frac{2}{3}=0 \ y= sqrt[3]{x+3}  \ -3y^2+3y+3=0 \ y^2-y-1=0 \ D=b^2-4ac=(-1)^2-4*1*(-1)=5 \ y_1= frac{-(-1)- sqrt{5}}{2*1}= frac{1- sqrt{5} }{2}   \ y_2= frac{-(-1)+ sqrt{5}}{2*1}= frac{1+ sqrt{5} }{2}   \  \  sqrt[3]{x+3}= frac{1}{2}+ frac{ sqrt{5} }{2} \ x+3=( frac{1}{2}+ frac{ sqrt{5} }{2})^3               x=( frac{1}{2}+ frac{ sqrt{5} }{2})^3-3= frac{1}{8}+ frac{3 sqrt{5} }{8}+ frac{15}{8}+ frac{ sqrt{5}^3 }{8}- frac{24}{8}= \  frac{ sqrt{5}(3+ sqrt{5}^2) -8}{8}= frac{8( sqrt{5}-1) }{8}= sqrt{5}-1

Приложения:
Похожие вопросы